2021
DOI: 10.1080/00346764.2020.1870710
|View full text |Cite
|
Sign up to set email alerts
|

Public health systems in the age of financialization: lessons from the French case

Abstract: Public Health Systems (PHS) are under continuous transformation in line with economic, political, and ideological changes in capitalist economies. The current stage of capitalism is underpinned by the process of financialization, meaning an increasing dominance of financial actors, markets, practices, measurements, and narratives over other agents, including the State. This article examines how financialization has been reshaping PHS, with an in-depth study of the French case. First, we suggest how to incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…22 Financialization in health care services is associated with a growing role for financial actors in social reproduction as they seek new profit opportunities. Research has shown its variegated nature in health systems in Turkey, 23 France, 24 lower-income countries, 25 and England's social care system. 26 Despite variations, some common themes emerge, with financialization associated with growing inequalities.…”
Section: Background and Approachmentioning
confidence: 99%
“…22 Financialization in health care services is associated with a growing role for financial actors in social reproduction as they seek new profit opportunities. Research has shown its variegated nature in health systems in Turkey, 23 France, 24 lower-income countries, 25 and England's social care system. 26 Despite variations, some common themes emerge, with financialization associated with growing inequalities.…”
Section: Background and Approachmentioning
confidence: 99%
“…En ce qui concerne l'hôpital, la dynamique de financiarisation est étudiée par celle de la dette de l'hôpital public qui en étant « autonomisé » et « responsabilisé », a contracté des emprunts toxiques (Juven et Lemoine, 2018, Juven et al, 2019. La dette hospitalière comme l'ensemble de la dette de la Sécurité Sociale fait l'objet d'une financiarisation qui prend la forme « d'innovations financières » (tels l'émission d'obligations) (Cordilha, 2021). Cette politique de la dette renforce le pouvoir des marchés financiers.…”
Section: -Financiariser Pour Mieux Transformerunclassified
“…La financiarisation ne se limite pas à la financiarisation des entreprises privées mais elle s'étend au public (Cordilha, 2021). En France, comme dans d'autres pays, les déficits et les dettes des comptes sociaux sont devenus des placements rentables pour les marchés financiers.…”
Section: La Santé éLément Du Capitalisme Financiariséunclassified